PERAN MODEL PEMBELAJARAN SAINS SD BERMUATAN DAKWAH TERHADAP PEMBENTUKAN SIKAP POSITIF SISWA: SYSTEMATIC LITERATURE REVIEW - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a Systematic Literature Review (SLR) aimed at examining the role of a da'wah-infused elementary science learning model in developing positive attitudes the elementary school students. The research method used included a systematic search, selection, and evaluation of relevant scientific articles published nationally and internationally between 2015 and 2025. The research subjects were 40 articles selected based on their relevance to the topic of developing positive attitudes in students through da'wah-infused science learning. Data collection techniques were carried out by identifying and extracting important information from these articles, particularly regarding the positive attitudes developed in students. Data analysis techniques included synthesizing and categorizing the findings based on the research questions. The results showed that 26 positive attitudes developed through the implementation of this learning model, with spirituality and responsibility being the most dominant, followed by empathy, honesty, and cooperation. Conclusion: The integration of da'wah values ​​in science learning plays a significant role in fostering positive attitudes and shaping the character of elementary school students. Further development and implementation of this learning model is recommended to strengthen character education at the elementary level.